Studi Antisipasi Perilaku Pelecehan Seksual Oleh Mahasiswa PPKn FKIP Universitas Mulawarman - Nurul Hikmah; A. Hardoko; M. Jamil; Novita Majid (Jurnal Pendidikan Anak Usia Dini dan Kewarganegaraan, 2025)
Higher education is a scientific institution which has the task of carrying out education and teaching above secondary level as well as providing education and teaching based on Indonesian national culture in a scientific manner. Sexual harassment behavior is an act of harassment that can occur directly or indirectly. Where the action involves another person in unwanted sexual activity, either verbally, or actions carried out by someone to control or manipulate another person. In general, the perpetrator of sexual harassment feels that he has power that can dominate the victim, and instills that there is nothing the victim can do, because the perpetrator has certain power. Sexual harassment on campus occurs due to a legal vacuum in preventing, handling and protecting victims of sexual harassment in the tertiary environment. In cases of sexual harassment that occur among students, it can occur due to a lack of education and counseling regarding sexual activity, it can also be caused by environmental factors where the perpetrator of the harassment feels they have the opportunity to carry out acts of harassment in the university environment. This research was conducted using qualitative methods which included observation, in-depth interviews, researchers have explored the nuances and complexities related to these issues, and researchers are ready to understand perceptions and anticipatory strategies regarding whether or not the Pancasila and Citizenship Education (PPKn) study program can help in handling sexual harassment by PPKn students at FKIP Mulawarman University.